A bottom-up synthesis of rare-earth-hydrotalcite monolayer nanosheets toward multimode imaging and synergetic therapy. Issue 25 (6th June 2018) - Mei, Xuan; Ma, Jialing; Bai, Xue; Zhang, Xin; Zhang, Shaomin; Liang, Ruizheng; Wei, Min; Evans, David G.; Duan, Xue
Abstract : Gd 3+ and Yb 3+ co-doped LDH monolayer nanosheets are developed via a facile "bottom-up" method and exhibit excellent drug loading capacity for tri-mode imaging guided cancer therapy. Abstract : Recently, ultrathin two-dimensional (2D) nanomaterials have attracted considerable research interest in biomedical applications, owing to their intriguing quantum size and surface effects. In this work, a one-step "bottom-up" method is developed to prepare rare-earth (Gd 3+ and Yb 3+ ) co-doped layered double hydroxide (LDH) monolayer nanosheets, with a precisely controlled composition and uniform morphology. Due to the successful introduction of Gd 3+ and Yb 3+ into the LDH host layer, the Gd&Yb-LDH monolayer nanosheets exhibit excellent magnetic resonance (MR)/X-ray computed tomography (CT) dual-mode imaging functionality. Moreover, the Gd&Yb-LDH monolayer nanosheets achieve an ultrahigh loading of a chemotherapeutic drug (SN38) with a loading content (LC) of 925%, which is a one order of magnitude enhancement compared with previously reported delivery systems of hydrophobic drugs. Interestingly, by further combination with indocyanine green (ICG), in vivo tri-mode imaging, including CT, MR and near infrared fluorescence (NIRF) imaging, is achieved, which enables a noninvasive visualization of cancer cell distribution with deep spatial resolution and high sensitivity. In addition, in vitro and in vivo therapeutic evaluations demonstrate an extremely high tri-mode synergetic anticancer activity and superior biocompatibility of SN38&ICG/Gd&Yb-LDH. Therefore, this work demonstrates a paradigm for the synthesis of novel multifunctional 2D monolayer materials via a facile "bottom-up" route, which shows promising applications in cancer synergetic theranostics.